Tumor-targeting Salmonella typhimurium A1-R suppressed an imatinib-resistant gastrointestinal stromal tumor with c-kit exon 11 and 17 mutations - Kentaro Miyake; Kei Kawaguchi; Masuyo Miyake; Ming Zhao; Tasuku Kiyuna; Kentaro Igarashi; Zhiying Zhang; Takashi Murakami; Yunfeng Li; Scott D. Nelson; Michael Bouvet; Irmina Elliott; et al. (Heliyon, 2018)
Gastrointestinal stromal tumor (GIST) is a refractory disease in need of novel efficacious therapy. The aim of our study was to evaluate the effectiveness of tumor-targeting Salmonella typhimurium A1-R (S. typhimurium A1-R) using on a patient derived orthotopic xenograft (PDOX) model of imatinib-resistant GIST. The GIST was obtained from a patient with regional recurrence, and implanted in the anterior gastric wall of nude mice. The GIST PDOX mice were randomized into 3 groups of 6 mice each when the tumor volume reached 60 mm3: G1, control group; G2, imatinib group (oral administration [p.o.], daily, for 3 weeks); G3, S. typhimurium A1-R group (intravenous [i.v.] injection, weekly, for 3 weeks). All mice from each group were sacrificed on day 22. Relative tumor volume was estimated by laparotomy on day 0 and day 22. Body weight of the mouse was evaluated 2 times per week. We found that S. typhimurium A1-R significantly reduced tumor growth in contrast to the untreated group (P = 0.001). In addition, we found that S. typhimurium A1-R was more effective compared to imatinib (P = 0.013). Furthermore, Imatinib was not significantly effective compared to the control group (P = 0.462). These results indicate that S. typhimurium A1-R may be new effective therapy for imatinib-resistant GIST and therefore a good candidate for clinical development of this disease.